Energy drinks available in Ireland: a description of caffeine and sugar content. Issue 9 (25th April 2017) - Keaver, Laura; Gilpin, Susannah; Fernandes da Silva, Joana Caldeira; Buckley, Claire; Foley-Nolan, Cliodhna
Abstract: Objective: To describe the caffeine and sugar content of all energy drinks available on the island of Ireland. Design: Two retail outlets were selected from each of: multinational, convenience and discount stores in Northern Ireland and the Republic of Ireland, and all available single-serve energy drinks were purchased. The cross-sectional survey was conducted in February 2015 and brand name, price, volume, caffeine and sugar content were recorded for each product. Descriptive analysis was performed. Results: Seventy-eight products were identified on the island of Ireland (regular, n 59; diet/sugar-free/light, n 19). Caffeine and sugar content was in the range of 14–35 mg and 2·9–15·6 g per 100 ml, respectively. Mean caffeine content of 102·2 mg per serving represents 25·6 % of the maximum intake advised for adults by the European Food Safety Authority. Per serving, mean sugar content of regular energy drinks was 37 g. This exceeds WHO recommendations for maximum daily sugar intake of <5 % of total energy intake (25 g for adults consuming 8368 kJ (2000 kcal) diet). If displaying front-of-pack labelling, fifty-seven of the fifty-nine regular energy drinks would receive a Food Standards Agency 'red' colour-coded label for sugar. Conclusions: Energy drinks are freely available on the island of Ireland and all products surveyed can be defined as highly caffeinated products. This has potential health issues particularly for children and adolescents where safe limits of caffeine have not been determined. Energy drinks surveyed also contained high levels of sugar and could potentially contribute to weight gain and adverse dental health effects.